Mechanism of herpesvirus protein kinase UL13 in immune escape and viral replication - Zhou, Lin; Cheng, Anchun; Wang, Mingshu; Wu, Ying; Yang, Qiao; Tian, Bin; Ou, Xumin; Sun, Di; Zhang, Shaqiu; Mao, Sai; Zhao, Xin-Xin; Huang, Juan; et al. (Frontiers in Immunology, 2022)
Upon infection, the herpes viruses create a cellular environment suitable for survival, but innate immunity plays a vital role in cellular resistance to viral infection. The UL13 protein of herpesviruses is conserved among all herpesviruses and is a serine/threonine protein kinase, which plays a vital role in escaping innate immunity and promoting viral replication. On the one hand, it can target various immune signaling pathways in vivo, such as the cGAS-STING pathway and the NF-κB pathway. On the other hand, it phosphorylates regulatory many cellular and viral proteins for promoting the lytic cycle. This paper reviews the research progress of the conserved herpesvirus protein kinase UL13 in immune escape and viral replication to provide a basis for elucidating the pathogenic mechanism of herpesviruses, as well as providing insights into the potential means of immune escape and viral replication of other herpesviruses that have not yet resolved the function of it.